Into the Abyss: a study to inform and develop a bespoke athlete transition model for professional rugby. Part 1: establishing a theoretical framework to guide the investigation - Thomas, B.; Grecic, D. (Journal of Qualitative Research in Sports Studies, 2020)
A real-world challenge was identified by the first author in how to create a bespoke athlete transition model for his professional rugby club. To guide the study a theoretical framework was sought to direct the data collection and analysis stages of the investigation. Established Talent Development (TD) research from other sports and TD environments is presented along with the authors` reflections on the literature to demonstrate the iterative process of developing their own theoretical framework. The intention was to shine a light in this research process so that both students and novice researchers could better understand the considerations that underpin this process within such a study. The product of this process is presented, that is, the C.A.R.E. Transition model, which embeds and reflects the various best practice TD influences explored and assimilated by the authors. This model will now form the basis of future research into this phenomenon.